CODE-SWITCHING AND CODE-MIXING IN ELT - Darwis, Aswinda (Journal of Language, Literature and Teaching, 2023)
AbstractThe study aimed to analyze Code-switching and Code-mixing between English and Indonesian language used by the lecturer in teaching the subject Communicative English Grammar for the second semester students of English education department of STAI DDI Pinrang.The method applied was qualitative descriptive. The data source was the utterances of the lecturer in teaching Communicative English Grammar. The data were collected by recording what the lecturer uttered in teaching-learning process and interviewing the lecturer to gain information about the functions of switching and mixing his code in teaching-learning process. Then, the collected data were classified and analyzed based on the types of code-switching and code-mixing and the functions based on the theory of Hoffman. The results showed that:1. The types of code-switching used by the lecturer of Communicative English Grammar in teaching and learning process were: inter-sentential, intra-sentential, and emblamatic/tag switching, and establishing continuity with the previous speaker. while for the types of code-mixing were: intra-sentential code mixing, intra-lexical code mixing, and involving a change of pronunciation; 2. The Functions or reasons of using both code-switching and code-mixing by the lecturer of Communicative English Grammar were: Repetition used for clarification, Intention of clarifying the speech content for students, and interjection. The findings implied that both code-switching and code-mixing were used by the communicative English grammar lecturer in English teaching-learning process, so it showed that both code-switching and code-mixing are necessary to facilitate ELT particularly in complicated subjets like grammar. In other words, the lecturers should consider the usage of both of them to meet the objectives of ELT.Keywords: Code-Switching, Code-Mixing, English Language Teaching